2023
DOI: 10.3389/fimmu.2023.1159743
|View full text |Cite
|
Sign up to set email alerts
|

Targeting RIPK1 kinase for modulating inflammation in human diseases

Abstract: Receptor-Interacting Serine/Threonine-Protein Kinase 1 (RIPK1) is a master regulator of TNFR1 signaling in controlling cell death and survival. While the scaffold of RIPK1 participates in the canonical NF-κB pathway, the activation of RIPK1 kinase promotes not only necroptosis and apoptosis, but also inflammation by mediating the transcriptional induction of inflammatory cytokines. The nuclear translocation of activated RIPK1 has been shown to interact BAF-complex to promote chromatin remodeling and transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 153 publications
0
8
0
Order By: Relevance
“…Recent preclinical and clinical studies have unquestionably recognized the roles of RIPK1 in neurogenerative disorders ( Li & Yuan, 2023 ; Scarpellini et al, 2023 ; Xu, Zhang & Zhuang, 2023 ). In a phase I clinical trial, a small molecule GFH312 showed significant RIPK1 inhibition with a tolerability profile comparable to that of the placebo ( Lickliter et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent preclinical and clinical studies have unquestionably recognized the roles of RIPK1 in neurogenerative disorders ( Li & Yuan, 2023 ; Scarpellini et al, 2023 ; Xu, Zhang & Zhuang, 2023 ). In a phase I clinical trial, a small molecule GFH312 showed significant RIPK1 inhibition with a tolerability profile comparable to that of the placebo ( Lickliter et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been extensively studied in the context of necroptosis, a programmed form of necrosis triggered by death-domain receptors (DRs) and executed in the absence of caspase activity. RIPK1 inhibition has emerged as a prime target in various neurodegenerative disorders, including AD, PD, and HD ( Degterev, Ofengeim & Yuan, 2019 ; Li & Yuan, 2023 ; Xu, Zhang & Zhuang, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, UA can induce cell damage through the activation of inflammatory responses and oxidative stress. On the other hand, UA can also affect the function of the immune system, including leukocyte migration and cytokine production (6). Therefore, UA may play a role in regulating the development of sepsis-induced inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicated that the initial serum UA levels during hospitalization should serve as a predictive indicator for the prognosis of sepsis in the pediatric intensive care unit (ICU) (5). Serum UA may play an important role in inflammatory responses, oxidative stress, and immune regulation (6). Inflammation caused an increase in the release of purines within cells, which in turn promoted the production and release of UA (7).…”
Section: Introductionmentioning
confidence: 99%
“…(I) Necrostatin-1 (Nec-1) is a potent and specific small-molecule inhibitor of receptor-interacting serine/threonineprotein kinase 1 (RIPK1). RIPK1, through its kinase and scaffolding functions, is a key regulator of apoptosis, necroptosis, and inflammatory pathways [163,164]. (J) The compound z-VAD-FMK (zVAD) is a cell-permeant pan-caspase inhibitor that irreversibly binds to the catalytic site of caspase proteases and can inhibit the induction of apoptosis [165].…”
Section: Therapeutic Targeting Of Clec16amentioning
confidence: 99%